Relationship between chronological and bone ages and pubertal stage of breasts with bone biomarkers and bone mineral density in adolescents - Cristina Maria Teixeira Fortes; Tamara Beres Lederer Goldberg; Cilmery Suemi Kurokawa; Carla Cristiani Silva; Maria Regina Moretto; Talita Poli Biason; Altamir Santos Teixeira; Hélio Rubens de Carvalho Nunes (Jornal de Pediatria (Versão em Português), 2014)
Objective: To study bone mineral density (BMD) in adolescent females according to five groups of chronological age (CA), bone age (BA), and breast development stage (B), and to correlate these parameters with plasma bone biomarkers (BB). Methods: This was a cross‐sectional study performed in 101 healthy adolescent females between 10 and 20 years old. The study variables were: weight, height, body mass index (BMI), CA, B, BA, calcium intake, BMD, and BB. Osteocalcin (OC), bone alkaline phosphatase (BAP), and C‐terminal telopeptide (S‐CTx) were evaluated for BB. BMD was measured using dual energy X‐ray absorptiometry (DXA). Results: BMD in lumbar spine, proximal femur, and total body increased with age, and the respective observed averages were: in CA1 (10 years old), 0.631, 0.692, 0.798 g/cm2; in CA2 (11 to 12 years old), 0.698, 0.763, 0.840 g/cm2; in CA3 (13 to 14 years old), 0.865, 0.889, 0.972 g/cm2; in CA4 (15 to 16 years old), 0.902, 0.922, 1.013 g/cm2; and in CA5 (17 to 19 years old), 0.944, 0.929, 1.35 g/cm2. These results showed significant differences between 13 and 14 years of age (CA3) or when girls reached the B3 stage (0.709, 0.832, 0.867 g/cm2). The highest median concentrations of BB were between 10 and 12 years of age when adolescents were in the B2–B3 (p < 0.001). Median BB concentrations decreased in advanced BA and B. Conclusions: BB concentrations were positively correlated with the peak height velocity and negatively correlated with BMD in the study sites. Increased BMD and BB concentrations were observed in B3.